All-Dielectric Metalenses for Long-Wavelength Infrared Imaging Applications: A Review - Shinpei Ogawa; Misaki Hanaoka; Manabu Iwakawa; Shoichiro Fukushima; Masaaki Shimatani (Sensors)
Infrared imaging has gained considerable attention across diverse fields, including security, surveillance, and environmental monitoring. The need to minimize size, weight, power, and cost (SWaP-C) poses challenges for conventional optical systems like refractive lenses. Metalenses with subwavelength surface patterns have emerged as promising solutions to address these limitations. This review provides a comprehensive analysis of all-dielectric metalenses for long-wavelength infrared (LWIR) imaging applications, a critical spectral region for human detection and analytical applications (such as gas analysis). We examine the limitations of conventional infrared (IR) lens materials and highlight the performance advantages of LWIR metalenses. Key design principles, including chromatic and achromatic lens configurations, are discussed alongside their imaging performance. Additionally, we review advanced functionalities such as polarization control, multifocal capabilities, zoom, and reconfigurability. Theoretical performance limits and trade-offs are analyzed to provide insights into design optimization. We identify future challenges related to advanced design methods and fabrication techniques. LWIR metalenses can be expected to overcome the shortcomings of conventional LWIR lenses owing to meta-optics technologies, to achieve SWaP-C and advanced functionalities that cannot be achieved by conventional LWIR lenses. This review will guide researchers in academia and industry to develop LWIR metalenses to advance IR imaging technologies.